Eu3+-activated SrY2O4:Ce4+/3+ red-phosphor for WLEDs: Structural and luminescent insights from experimental and theoretical approaches - Saraiva, Leonardo F. [UNESP]; Bispo-Jr, Airton G.; Lima, Sergio A.M. [UNESP]; Pires, Ana M. [UNESP] (Elsevier, 2023)
Herein, single-phase Eu3+-activated SrY2O4:Ce4+/3+ red-emitting phosphor was produced by an adapted Pechini route under softer synthesis conditions (1100 °C in CO reducing atmosphere) compared to those reported so far. A detailed structural study conducted by Rietveld refinement and DFT calculations confirmed the presence of two hexa-coordinated Y3+ sites that are occupied by Eu3+. Cerium is present in a mixed oxidation state, where the proportion of Ce4+/Ce3+ was determined as 70/30% by X-ray photoelectron spectroscopy (XPS), and this influences the SrY2O4 phase stabilization by increasing the point defect concentration. A thorough analysis of the photoluminescent features of Eu3+-activated phosphor revealed its occupancy in at least two non-equivalent local sites belonging to the C1 point group. Furthermore, the excited state dynamics of the phosphors were enlightened by the theoretical band structure determination. Finally, 3%-doped sample exhibited the highest intrinsic quantum yield (81%), which qualifies these materials to be used as red-emitting components for solid-state lighting.
Keywords: Cerium(IV/III); Eu(III) activator ion; Luminescence spectroscopy; Single and multireference calculations; Strontium and yttrium oxide